2020
DOI: 10.1021/acsnano.0c01300
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated H2 Nanogenerator for Enhanced Chemotherapy of Bladder Cancer

Abstract: Hydrogen gas can mitigate oxidative stress in many diseases and is regarded to be safe and free of side effects. Inspired by a metalloenzyme in a variety of microorganisms, here, we propose a photoactivated H 2 nanogenerator that comprises a fluorinated chitosan (FCS), a chemotherapeutic drug (gemcitabine, GEM), and a catalyst of H 2 production ([FeFe]TPP) that can form self-assembled [FeFe]TPP/GEM/ FCS nanoparticles (NPs). The [FeFe]TPP/GEM/FCS NPs exhibit excellent transmucosal and tumor cell penetration cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 62 publications
(84 reference statements)
0
49
0
Order By: Relevance
“…FCS was synthesized by grafting the fluoroalkane chains to CS via amide coupling following our reported protocol. [23,24] CS was used to prepared Cu 2-x Se@CS (CC) NPs as non-fluorinated counterparts as the control. The morphologies and sizes of the as-prepared CC and CF NPs were examined by transmission electron microscopy (TEM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FCS was synthesized by grafting the fluoroalkane chains to CS via amide coupling following our reported protocol. [23,24] CS was used to prepared Cu 2-x Se@CS (CC) NPs as non-fluorinated counterparts as the control. The morphologies and sizes of the as-prepared CC and CF NPs were examined by transmission electron microscopy (TEM).…”
Section: Resultsmentioning
confidence: 99%
“…[21] Our previous research has demonstrated that fluorinated cationic polymers including polyethylenimine and CS could form selfassembled nanoparticles with polypeptides, photosensitizers, or sonosensitizers for remarkably improving their transmucosal adsorption and tumor permeability in the bladder wall, which can further enhance the intravesical instillation therapy. [22][23][24] More specially, fluorinated CS (FCS) possesses high biocompatibility for intravesical instillation and could reversibly modulate the tight junctions of bladder epithelium for effectively transmucosal delivery of drugs. [23] Therefore, we reason that the binding with FCS would remarkably enhance the penetration of photothermal agents in the bladder to achieve potent PTT for BCa treatment.…”
Section: Introductionmentioning
confidence: 99%
“…have synthesized a photoactivated H 2 nanogenerator comprising [FeFe]‐hydrogenase, fluorinated chitosan (FCS), and gemcitabine (GEM). FCS was used to improve the transmembrane and transmucosal delivery of the nanogenerator 132 . Meanwhile, GEM together with [FeFe]TPP realizes controlled H 2 release within tumors under laser (660 nm) irradiation, thus significantly enhancing the efficacy of intravesical instillation chemotherapy.…”
Section: Strategies For Generating Gasmentioning
confidence: 99%
“…(D) A photo‐activated H 2 nanogenerator capable of enhancing chemotherapy for bladder cancer. Reproduced with permission 132 . Copyright 2020, American Chemical Society.…”
Section: Gas‐based Nanomedicines For Enhanced Cancer Therapymentioning
confidence: 99%
“…88 Since then, H 2 therapy has received much attention for the treatment of cancer and other inflammatory diseases. [89][90][91] The use of H 2 -rich water and saline has been tested in more than 50 clinical trials on several oxidative stressrelated/inflammatory diseases, including type II diabetes mellitus, stroke, Parkinson's disease, and cancer. [92][93][94] However, it is inconvenient to accurately control gas delivery to the diseased areas with macroscopic administration.…”
Section: Ucnp-based H 2 Gas Therapymentioning
confidence: 99%